(untitled) (Research, Society and Development, 2020)
Objective: To analyze the prevalence of olfactory and gustatory disorders present in COVID-19 and its implications for patients. Methods: Integrative literature review carried out by searching the databases of Latin American and Caribbean Literature in Health Sciences, Medical Literature Analysis and Retrieval System Online and Scientific Electronic Library Online. The descriptors were combined in pairs in "Olfaction Disorders AND COVID-19" and "Ageusia AND COVID-19". Articles available in full, in Portuguese, English and Spanish were included; originals and systematic reviews; published from January to August 1, 2020; with cohesive and well-designed methodology. Integrative and bibliographic review articles with duplication in the databases were excluded. Results: The final sample consisted of 10 articles. A table was prepared with the year of publication, authors, country, type of article, level of evidence and objective of the studies. Conclusion: Olfactory and gustatory dysfunctions are common indicators of COVID-19 infection and can develop at the beginning of the clinical picture, persisting or not after the end of treatment. Thus, individuals should be guided by health professionals about the need for social isolation and adequate treatment, aiming at interrupting the transmission of the infectious agent.